IDLN-MSP: Idiolocal normalization of real-time methylation-specific PCR for genetic imbalanced DNA specimens. (February 2016) - Santourlidis, Simeon; Ghanjati, Foued; Beermann, Agnes; Hermanns, Thomas; Poyet, Cédric
Sensitive, accurate, and reliable measurements of tumor cell-specific DNA methylation changes are of fundamental importance in cancer diagnosis, prognosis, and monitoring. Real-time methylation-specific PCR (MSP) using intercalating dyes is an established method of choice for this purpose. Here we present a simple but crucial adaptation of this widely applied method that overcomes a major obstacle: genetic abnormalities in the DNA samples, such as aneuploidy or copy number variations, that could result in inaccurate results due to improper normalization if the copy numbers of the target and reference sequences are not the same. In our idiolocal normalization (IDLN) method, the locus for the normalizing, methylation-independent reference amplification is chosen close to the locus of the methylation-dependent target amplification. This ensures that the copy numbers of both the target and reference sequences will be identical in most cases if they are close enough to each other, resulting in accurate normalization and reliable comparative measurements of DNA methylation in clinical samples when using real-time MSP.